22. PROPHYLACTIC EFFECT OF VARYING PHENYLEPHRINE DOSE ON HYPOTENSION DURING BEACH CHAIR POSITION IN SHOULDER ARTHROSCOPY: A RANDOMIZED CONTROLLED TRIAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of Phenylephrine in preventing positional hypotension during arthroscopic shoulder surgery in the sitting position.Subjects and methods: This was a randomized controlled clinical trial involving 105 patients undergoing arthroscopic shoulder surgery, divided into three groups: control group, Phenylephrine infusion at a dose of 1,0 mcg/kg/min, and Phenylephrine infusion at a dose of 1,5 mcg/kg/min.Results: The control group had a higher incidence and average number of hypotensive episodes compared to both intervention groups (100% vs. 74,3% and 91,4%, p < 0,05; 3,83 ± 1,04 time vs. 1,92 ± 1,06 time and 1,66 ± 0,70 time; p < 0,05). Systolic blood pressure, diastolic blood pressure, and mean arterial pressure in the control group were significantly lower than in both intervention groups after positional change (p < 0,05). The average dose of ephedrine used in the control group was 3,35 times higher than the 1.0 mcg/kg/min group and 2,44 times higher than the 1,5 mcg/kg/min group (p < 0,05). The 1,0 mcg/kg/min Phenylephrine group showed comparable effectiveness in preventing hypotension to the 1.5 mcg/kg/min group, but with significantly fewer adverse events related to Phenylephrine (bradycardia, hypertension) and more stable mean arterial pressure (p < 0,05). Baseline characteristics including age, sex, weight, and comorbidities were not significantly different between groups.Conclusion: Phenylephrine is effective in reducing the incidence and severity of beach chair position-related hypotension. The continuous infusion of Phenylephrine at 1,0 mcg/kg/min provides effective prophylaxis with fewer adverse effects compared to the higher dose, 1,5 mcg/kg/min.
Keywords: Anesthesia, hypotension, shoulder arthroscopy, Phenylephrine.